They planted the Cape : III (Historia, 2021)
Van Riebeeck .reported to the Lords Seventeen that a remarkable harvest had been won for the season 1658-59, and writing in January 1659 assures them "that matters are in a desirable state here. ...so that at present we not only have abundance, but can also -depend upon ourselves alone, and are beginning to have something over. .."He describes the granary he has built at Rondebosch as "like a small church". (It measured 108 feet by 40 feet.
Keywords: Van Riebeeck; Agriculture; Grain; Cape; Grapes; Farming